The Revival of the Notion of Finesse: the Comprehension of the Dialogue between an Artistic Image and an Intellectual Idea in Modern Architecture - Volchok, Yury P. (Actual Problems of Theory and History of Art, 2016)
The revival of the notion of finesse has become a new task in terms of historical and theoretical issues related to architectural criticism. The aim of this article is its integration into the framework of nonlinear world perception. The revival of the classic interpretation of finesse, which according to H. Poincaré is the product of harmoniously wholesome internal structure, allows us to fill the visual perception of architecture with intellectual contents. The application of this notion may become the basis for the essentially “fine” dialogue between the two concepts that drifted apart relatively long ago — “history” and “evolution” taken within the logic of “Grand-Time Architectonics” (M. M. Bakhtin).